2010
DOI: 10.1097/nmd.0b013e3181f97be3
|View full text |Cite
|
Sign up to set email alerts
|

Late Mental Health Changes in Tortured Refugees in Multidisciplinary Treatment

Abstract: The aim of this study was to examine long-term changes in symptoms of post-traumatic stress disorder, depression, anxiety, and in health-related quality of life in traumatized refugees 23 months after admission to multidisciplinary treatment. The study group comprised 45 persons admitted to the Rehabilitation and Research Centre for Torture Victims in 2001 to 2002. Data on background, trauma, present social situation, mental symptoms (Hopkins Symptom Checklist-25, Hamilton Depression Scale, Harvard Trauma Ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 31 publications
2
35
1
Order By: Relevance
“…It is well-known that specialized treatment centres often admit treatment-resistant refugees with higher symptom severity (Drozdek, 2015). In fact, the mean scale score of the investigated sample is comparable to those of other intervention studies on traumatized refugees in specialized treatment centres in terms of symptoms of depression, anxiety and PTSD (Carlsson et al, 2010; Neuner et al, 2010; Schock, Bottche, Rosner, Wenk-Ansohn, & Knaevelsrud, 2016). Thus, the results of the current study should be interpreted against this background.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…It is well-known that specialized treatment centres often admit treatment-resistant refugees with higher symptom severity (Drozdek, 2015). In fact, the mean scale score of the investigated sample is comparable to those of other intervention studies on traumatized refugees in specialized treatment centres in terms of symptoms of depression, anxiety and PTSD (Carlsson et al, 2010; Neuner et al, 2010; Schock, Bottche, Rosner, Wenk-Ansohn, & Knaevelsrud, 2016). Thus, the results of the current study should be interpreted against this background.…”
Section: Discussionsupporting
confidence: 77%
“…To our knowledge only one multidisciplinary treatment study analysed changes in quality of life and found improvements only in the environmental scores from pre- to 9-months assessment (Carlsson et al, 2010). Also in other types of intervention studies, quality of life was rarely investigated and yielded inconsistent results (Buhmann et al, 2015; Ter Heide, Mooren, Kleijn, de Jongh, & Kleber, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…No treatment effect was found for PTSD, depression or quality of life. At the 23-month follow-up, Carlsson et al 18 found that approximately 1/3 of the participants reported reliable symptom improvement as measured by self-report.…”
Section: Introductionmentioning
confidence: 99%